Pengaruh Faktor Budaya, Faktor Sosial Dan Faktor Pribadi Terhadap Keputusan Pembelian Jasa Pada PT. Telkom Kota Metro - Fuadi, Selamet; Kusmawati, Nanda; Novrianda, Herry (Universitas Muhammadiyah Metro, 2023)
In line with the rapid economic growth of Indonesia, the demand for telecommunicationsservices is also increasing, so that PT Telkom Indonesia must be able to serve the needs ofthe community by increasing the number of connection units and the quality oftelecommunication facilities. This improvement effort has been carried out by implementingPT Telkom's policies, namely, the best service, the best image and the best results. All aredirected to customer satisfaction of PT Telkom service users. This study aims to determine 1)To determine whether cultural factors influence purchasing decisions. 2) To find out whetherthere is an influence of social factors on purchasing decisions. 3) To find out whether there isan influence of personal factors on purchasing decisions. 4) To find out whether there is aninfluence of cultural factors, cultural factors, personal factors, social factors together onpurchasing decisions. The survey method was chosen as the primary data source. The surveymethod focuses on collecting data from respondents who have certain information, thus enabling researchers to solve problems. Data collection was carried out using a questionnaireor questionnaire instrument. Based on the estimated time and limitations, the population inthis study were all wifi users from Telkom Indonesia on metrp. then the population is takenbased on the largest number of buyers in a year in 2020, which is as many as 133 buyers. Theresults show that 1) there is a positive and significant influence between cultural factors onpurchasing decisions 2) there is a positive and significant influence between social factors onpurchasing decisions. 3) there is a positive and significant influence between personal factorson purchasing decisions 4) there is a positive and significant influence between personalfactors on purchasing decisions. positive and significant influence between cultural factors,personal factors, social factors on purchasing decisions.